Influence of capping layer on skyrmion and domain-wall formation in Co/Pt(111) - (:unkn) unknown (My University, 2020)
In order to realize skyrmion-based next-generation logic and memory devices, investigating the impact ofmaterial parameters on skyrmion formation is essential. Capping magnetic thin layers for the purposes of both preventingoxidation and/or enhancing crystal structure has an influence on chiral spin texture of the layer. In this paper, we havecarried out a systematic computational study on magnetic skyrmion and domain-wall formation in which 2-atomic layerof Co, deposited on Pt(111) substrate and capped by certain (Ta, Ir, and Pt) 5delements with various thicknesses.We have determined the magnetic topography of the structures by simulations based on DFT-calculated parameters;micromagnetic Dzyaloshinskii-Moriya interaction, exchange interaction, and magnetic anisotropy coefficients. We haverevealed the influence of capping material and thickness on the chiral spin texture. We anticipate that our predictionsprovide a rational basis for skyrmion-based devices in which skyrmions are used as logic or information element.